Strategi Penguatan Pendidikan Multikultural di Lembaga Pendidikan Islam Indonesia: Analisis SWOT - Febrian, Vicky Rizki; Husmen, Ramza (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2025)
Indonesia is a multicultural nation characterized by ethnic, religious, cultural, and linguistic diversity, which requires the education system to manage differences in an inclusive and civilized manner. Multicultural education is considered a strategic approach to fostering tolerance, social justice, and national unity, particularly within Islamic educational institutions. However, its implementation in Indonesia still faces various challenges from both internal and external factors.This study aims to analyze the implementation of multicultural education in Islamic educational institutions in Indonesia using a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis to obtain a comprehensive understanding and formulate contextual strengthening strategies. The research employs a qualitative approach, with data collected through interviews, observations, and documentation. Data were analyzed through reduction, display, and categorization into a SWOT matrix.The findings indicate that the strengths of multicultural education lie in socio-cultural diversity, the ideological foundation of Pancasila, and national education policy support. Nonetheless, weaknesses persist in educators’ understanding, curriculum integration, and institutional inclusivity. Opportunities arise from religious moderation policies, educational technology development, and increasing public awareness, while threats include intolerance, radicalism, identity politicization, and negative digital media influences.